О влиянии доли нитрида тантала в твердых сплавах Т12А и Т23А на эффективность получения наноструктур при действии фемтосекундного лазера - Костюк, Геннадий Игоревич; Екасёва, Юлия Владимировна (НТУ "ХПИ", 2018)
На основе теоретического исследования влияния технологических параметров фемтосекундного лазера (плотность теплового потока, время облучения, радиус пятна контакта) на полученный объем нанокластера (НК) для твердых сплавов Т12А и Т23А сделаны следующие выводы: 1) с ростом плотности теплового потока, снижением времени его действия и размера радиуса пятна, объем НК, а следовательно и его размеры снижаются; 2) следует ожидать повышение физико-механических характеристик РИ. Размер зерна в сплаве Т23А несколько выше, что говорит о большой перспективе применения Т12А с наноструктурами, что подтверждается большей его твердостью чем у Т23А, т.е. увеличение доли нитрида тантала снижает твердость наноструктуры.

Based on the theoretical study of the influence of the technological parameters of a femtosecond laser (heat flux density, irradiation time, contact spot radius) on the obtained volume of a nanoclusters (NC) for hard alloys T1 2A and T23A, the following conclusions are drawn: 1) with an increase in the density of heat flow, a decrease in the time of its action and the size of the spot radius, the volume of the ND, and consequently its dimensions, decrease; 2) we should expect an increase in physico-mechanical characteristics of the RI. The grain size in the T23A alloy is somewhat higher, which indicates the long-term use of T12A with nanostructures, which is confirmed by its greater hardness than in T23A, i.e. an increase in the proportion of tantalum nitride reduces the hardness of the nanostructure.
On the influence of the fraction of tantalum nitride in hard alloys T12A and T23A on the efficiency of obtaining nanostructures under the action of a femtosecond laser
Keywords: нитрид тантала; наноструктуры; температурное напряжение; сплав; тепловой поток